2017
DOI: 10.3390/molecules22020285
|View full text |Cite
|
Sign up to set email alerts
|

High-Yield Production of Levulinic Acid from Pretreated Cow Dung in Dilute Acid Aqueous Solution

Abstract: Agricultural waste cow dung was used as feedstock for the production of a high value–added chemical levulinic acid (LA) in dilute acid aqueous solutions. A high LA yield of 338.9 g/kg was obtained from the pretreated cow dung, which was much higher than that obtained from the crude cow dung (135 g/kg), mainly attributed to the breakage of the lignin fraction in the lignocellulose structure of the cow dung by potassium hydroxide (KOH) pretreatment, and thus enhanced the accessibility of cow dung to the acid sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…Su et. al examined the in uence of HCl concentration on the production of LA and represented the results for 0.1, 0.2, 0.4, and 0.6 M HCl [30]. Their ndings are consistent with our study, and they concluded that maximum conversion succeeded with yields of LA as 309.7 and 338.9 g/kg at 0.4 and 0.6 M of HCl, respectively.…”
Section: Effects Of Ptsa Concentration On Levulinic Acid and Other Pr...supporting
confidence: 85%
See 2 more Smart Citations
“…Su et. al examined the in uence of HCl concentration on the production of LA and represented the results for 0.1, 0.2, 0.4, and 0.6 M HCl [30]. Their ndings are consistent with our study, and they concluded that maximum conversion succeeded with yields of LA as 309.7 and 338.9 g/kg at 0.4 and 0.6 M of HCl, respectively.…”
Section: Effects Of Ptsa Concentration On Levulinic Acid and Other Pr...supporting
confidence: 85%
“…As a result, the reaction may proceed more completely, leading to higher LA yields. Literature ndings support this trend [30,31]. In terms of weightbased yields of LA, they decreased sharply from 48.5 to 33.3% as the b/s ratio doubled.…”
Section: Effects Of Biomass To Solvent Ratio On Levulinic Acid and Ot...mentioning
confidence: 66%
See 1 more Smart Citation